IMPELEMENTASI KEPEMIMPINAN BERKELANJUTAN: MERANCANG MASA DEPAN YANG BERDAYA SAING DAN BERINTEGRITAS - Ari Prabowo; Jumeida Simatupang; Yahya Tanjung; Aisyah Azhar Adam; Shofyan Roni; Adam Saman Prakoso (Bajang Institute, 2024)
This seminar aims to provide students with an understanding of the importance of sustainable leadership, encourage students to develop competitive leadership skills, shape students' characters to become future leaders with integrity, inspire students to play an active role in sustainable development in the surrounding environment, and equip students with insights and practical skills needed in the modern era. Important targets of this seminar include students of SMA Negeri 19 Medan as future leaders, teachers and educators as facilitators in the development of student leadership, the school environment as an ecosystem that supports the implementation of sustainable leadership, and the surrounding community as beneficiaries of positive changes produced by young leaders. The method was conducted indoors using slides and presentations in front of the students. Some questions and answers about the material provided were held to make it easier for all students to understand and find out more about the material that had been delivered previously. The implementation of service activities took place in the SMA Negeri 19 Medan Hall starting at 09.00 WIB until completion, with 200 participants attending. Activities in the form of direct delivery of material. The results of the seminar activities are Overall, the results of community service activities in the form of this seminar showed a significant positive impact on SMA Negeri 19 Medan students. The seminar not only succeeded in improving students' understanding of sustainable leadership, but also inspired them to become future leaders with competitiveness and integrity. In addition, this activity encouraged students to take an active role in creating positive changes in the school environment and society. With support from all parties, the results of this seminar are expected to create a sustainable impact and give birth to a generation of leaders who are able to answer challenges in the modern era.